2017
DOI: 10.1093/cercor/bhx033
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Training-Related Plasticity by Combining fMRI and DTI: The Right Hemisphere Ventral Stream Mediates Musical Syntax Processing

Abstract: As a functional homolog for left-hemispheric syntax processing in language, neuroimaging studies evidenced involvement of right prefrontal regions in musical syntax processing, of which underlying white matter connectivity remains unexplored so far. In the current experiment, we investigated the underlying pathway architecture in subjects with 3 levels of musical expertise. Employing diffusion tensor imaging tractography, departing from seeds from our previous functional magnetic resonance imaging study on mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 98 publications
4
28
0
Order By: Relevance
“…The current data thus also manifest some gradual changes with expertise, as we could show before [4,6].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The current data thus also manifest some gradual changes with expertise, as we could show before [4,6].…”
Section: Discussionsupporting
confidence: 76%
“…The present study explored modulation of EEG brain oscillatory activities in several frequency ranges in people with 3 different levels of expertise in response to major and minor mode compositions. We expected first an effect of expertise revealed by differences in the degree of neuronal synchronization in low and high frequencies ranges [15,21,22], essentially in the right hemisphere [1,2,4,6,28,29].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Numerous studies in the domains of language, music, and vision have investigated the discrimination of hierarchical structures by asking participants to evaluate whether sequences of items are well‐formed according to a previously learned system of rules (Bahlmann, Schubotz, & Friederici, ; Bahlmann, Schubotz, Mueller, Koester, & Friederici, ; Bianco et al, ; Friederici, Bahlmann, Friedrich, & Makuuchi, ; Maess, Koelsch, Gunter, & Friederici, ; Sammler, Koelsch, & Friederici, ). These studies suggest that lateral prefrontal cortex (PFC, particularly inferior frontal gyrus, IFG) might contribute multi‐domain resources to the processing of hierarchies (Fadiga, Craighero, & D'Ausilio, ; Friederici et al, ; Patel, ), in interaction with areas along ventral visual/auditory streams that may store domain‐specific schematic information (Bianco et al, ; Martins et al, ; Oechslin, Gschwind, & James, ; Pallier, Devauchelle, & Dehaene, ; Sammler et al, ). Recent anatomical research has shown that IFG in humans is expanded (Schenker et al, ) and more strongly connected with the posterior temporal regions in comparison to other primates (Neubert, Mars, Thomas, Sallet, & Rushworth, ; Rilling et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, since playing a musical instrument constitutes a multidimensional task, the investigation of professional musicians can contribute to a better understanding of how the human brain integrates information from different modalities . Such integrative computational demands have previously been shown to abet architectural changes in several fiber bundles, including the corpus callosum, the arcuate fasciculus, the extreme capsule, and the corticospinal tract . Furthermore, since white matter alterations have an influence on the speed and synchrony of impulse transmission, musicians often demonstrate increased functional connectivity between brain regions essentially contributing to music performance .…”
Section: Music Training As a Window Into Brain Plasticitymentioning
confidence: 99%